Intellectual property rights in the light of Islamic law and man-made regulations - Moustafa Moursi, Abdel Wadoud; Laluddin, Hayatullah (Malayan Law Journal Sdn Bhd, 2010)
Intellectual property means the publication that is protected and remains as an exclusive right of its author. It is divided into two types. The first kind is auditory such as: sermons and lectures and its alike that are delivered orally. Customarily the right of this type of intellectual property belongs to all Muslims without any restriction. The second type is publication which means written material and documents in any field of sciences regardless of whether it belong to the theoretical science such as principles of Islamic jurisprudence sciences of Quran, tradition sciences of history, etc. or belonging to the experimental sciences such as Chemistry, Physics, Geometry, Medicine Pharmaceutical Science, etc. Scholars have used various terms that implies intellectual property, for example, the right of publication, the right of novelty, right of innovation or creativity, the right of intellectual benefits, the moral right, right of thought and the right of intellectual product